DISKURSUS MASYARAKAT MADANI, CIVIL SOCIETY DAN KHAERU UMMAH - Ramdani, Fauziah (Mekomda: Media Komunikasi Dakwah, 2025)
Civil society with its pluralism philosophically refers to a society that is in accordance with a strong frame of Islamic values The purpose of this research is to explore the relationship between the concepts of civil society, civil society, and khaeruh ummah in an Islamic context. Using library research with fifteen references, the study reveals several key findings. Firstly, civil society is seen as an ideal model practiced in Medina during the time of Prophet Muhammad, where pluralism and respect for differences were emphasised. Secondly, civil society and civil society have their own historical roots, although they share the common purpose of organizing social and state life. Thirdly, the desire to create a civilized and dignified society is closely connected to religion, which provides the main source of strength. Lastly, the concept of khaerul ummah, inspired by the verses of the Qur'an, serves as evidence of a civilized society that values humanism, freedom, and faith. Overall, this research highlights the importance of Islamic values in the formation of a pluralistic and dignified civil society.